Joyful Learning Meningkatkan Hasil Belajar Mahasiswa Fkip Umsu Pada Mata Kuliah Muamalah - Nur Sakinah; Uswah Hasanah (EDUTECH, 2021)
Joyful Learning Improves Learning Outcomes of FKIP UMSU Students in the Muamalah Course that learning is no longer understood as just a process of transferring knowledge but must be practiced by students. As a form of implementation of activities carried out by each student. This study aims to determine whether or not the effects of the problems faced in class are often not in line with expectations. It is in learning muamalah material that students often encounter boredom and difficulty accepting the material. So that students feel uncomfortable with learning so they will do things that can interfere with the learning process.This study aims to determine how much joyful learning is so that classroom learning in the implementation of learning should be held interactively, inspiring, fun, challenging and motivating students to participate actively. The implementation of learning is carried out in a fun way and can have a positive effect on student learning outcomes. Activities carried out by students are doing classroom practice using Joyful Learning.